Movie Still From The Pearl - RKO Radio Pictures:::Creator::::::::::::
The Pearl movie still of Kino (Pedro Armendariz) just after he has discovered that they are being followed. A Caption reads: THE PEARL Kino discovers they are being followed. This scene filmed in Acapulco de Juarez, Guerrero, Mexico, North America. RESTRICTED USE Original in safe